A Small-Area Solenoid Inductor Based Digitally Controlled Oscillator - Park, Hyung-Gu; Kim, SoYoung; Lee, Kang-Yoon (Journal of semiconductor technology and science, 2013)
This paper presents a wide band, fineresolutiondigitally controlled oscillator (DCO) withan on-chip 3-D solenoid inductor using the 0.13 μmdigital CMOS process. The on-chip solenoid inductoris vertically constructed by using Metal and Vialayers with a horizontal scalability. Compared to aspiral inductor, it has the advantage of occupying asmall area and this is due to its 3-D structure. Tocontrol the frequency of the DCO, active capacitorand active inductor are tuned digitally. To cover thewide tuning range, a three-step coarse tuning schemeis used. In addition, the DCO gain needs to becalibrated digitally to compensate for gain variations. The DCO with solenoid inductor is fabricated in 0.13μm process and the die area of the solenoid inductoris 0.013 mm2. The DCO tuning range is about 54 % at4.1 GHz, and the power consumption is 6.6 mW froma 1.2 V supply voltage. An effective frequencyresolution is 0.14 kHz. The measured phase noise ofthe DCO output at 5.195 GHz is -110.61 dBc/Hz at 1MHz offset. KCI Citation Count: 0